IMPLEMENTASI METODE COLLISION DETECTION PADA GAME STAR SHIP ADVENTURE - TRI PUASA PUTRA, 12.01.53.0051 (Information Technology and Telematics, 2017)
Abstract In its development, the game is built on several platforms one of which, a mobile device that uses the android operating system, which utilizes multiple methods of manufacture. In the field of game programming, Collision Detection or collision detection is a fundamental thing. Most of the games require this as the core of its game mechanic. Collision detection method can determine the position and slices that occur during an impact between objects. So that can give further effects after a collision between objects in the game. In this study the authors to design and build applications based game Star Ship Adventure android by applying collision detection. The application of collision detection function to detect collisions between objects in the game. The game is built using the Android SDK, Android Development Tools, and Eclipse IDE, the Java programming language. Results from this research that produces Android-based mobile game in the form of single player games that can be run on android smartphone. Keywords: Game, Android, Collision detection. Abstrak Pada perkembangannya saat ini, Game dibangun untuk beberapa platform salah satunya yaitu, perangkat mobile yang menggunakan  sistem operasi android, yang memanfaatkan beberapa metode dalam pembuatannya. Dalam bidang game programming, Collision Detection atau deteksi tumbukan adalah suatu hal yang mendasar. Hampir sebagian besar game membutuhkan hal ini sebagai inti dari game mechanic-nya. Metode collision detection dapat menentukan posisi dan irisan yang terjadi saat terjadi benturan antar objek. Sehingga dapat memberi efek-efek selanjutnya setelah terjadi benturan antar objek pada game. Dalam penelitian ini penulis merancang dan membangun aplikasi game Star Ship Adventure berbasis android dengan menerapkan collision detection. Penerapan collision detection berfungsi untuk mendeteksi tumbukan antar objek dalam game. Game ini dibangun menggunakan Android SDK, Android Development Tools, and Eclipse IDE, dengan bahasa pemrograman java. Hasil dari penelitian ini yaitu menghasilkan game mobile berbasis android berupa game single player yang dapat dijalankan pada smartphone android. Kata Kunci: Game, Android, Collision detection.